Strengthening Model of Institutional Capacity of Sugarcane Farmers in Situbondo Regency - Yuniati, Sri; Susilo, Djoko (SCAD Independent, 2019)
The institution of sugarcane farmers is one of mechanisms supporting economic activity in sugarcane agri-business. It has important role for increasing productivity and promoting bargaining position of sugarcane farmers. In fact, however, it is yet to functionate optimally. The research aimed at identifying institutional forms, analyzing inter-institutional interaction of sugarcane farmers, and formulating a model of capacity strengthening of sugarcane farmer’s institution. This research used case study approach. The institutional sampling method was performed purposively. Data were collected by using observation, interview, and documentation techniques. Data analysis was carried out using qualitative descriptive method. The results showed that the institution of sugarcane farmers comprises farmers group, sugarcane farmers cooperative, sugarcane farmers association, sugar processing industry, and supporting service institution. The circumstances of sugarcane farmer’s’ institution is more socio-cultural. It has not been fully directed to promote farmers’ access towards technology, capital, and market required for the development of sugarcane agri-business.